Dificuldades que os professores enfrentam para trabalhar a inclusão no ensino fundamental na E.M.E.F. Antonia Baldominio Regoso zona rural do município de Novo Repartimento/PA - ARAÚJO, Marta Ferreira de Freitas (2021)
This work has as its theme, "Difficulties that teachers face to work for inclusion in elementary school in E.M.E.F. Antonia Baldominio Regoso rural area of the municipality of Novo Repartimento / PA ". With the general objective to investigate the difficulties faced by teachers of the public school network of new repartition. The school is old and its structure is improper to work with inclusive education, moreover, it lacks the training of professionals and adequate materials to carry out such an activity. As for the specific objectives, reconstruct the history of special education phase of exclusion, segregation, integration to inclusion, verify public policies for inclusion and pedagogical practices, this was a research conducted at the School Antonia Baldomino Regoso, in which purpose of presenting the experiences and difficulties of teachers in working in a school that is not adapted to include students with educational needs. The results of the research showed that there is a lot to be done in relation to teacher training aimed at inclusion, as well as an architectural structuring in the school, investments in the area, adequate pedagogical materials and behavioral changes of all that directly or indirectly participate in the education.